A low-permeability high-viscosity silicone encapsulation adhesive and preparation method thereof
By using surface modification of nanosilicon dioxide in silicone packaging glue to form a crosslinking center, the problem of high vapor permeability of existing silicone packaging glue is solved, and both low permeability and high mechanical properties are achieved.
Patent Information
- Application Number
- CN202411723879.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-04
AI Technical Summary
The existing silicone packaging glue has a high water vapor permeability and cannot meet the requirements of optoelectronic devices for low water vapor permeability.
By using the method of surface modification of nanosilica, the surface of the nanosilica is coupled by a silane coupling agent with double bonds, and then the end-side double hydrogen-containing silicone oil is subjected to a hydrogen-silica addition reaction under the catalysis of the platinum catalyst. The hydrogen-containing silicone oil chain is grafted to form a cross-linking center and added to the silicone encapsulation glue to reduce the permeability of water vapor.
It effectively reduces the water vapor permeability of silicone packaging glue, and at the same time improves its mechanical properties and cross-linking degree, meeting the requirements of optoelectronic devices for low permeability and high mechanical properties.
Smart Images

Figure BDA0005158735900000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of organic silicon encapsulation adhesives, and in particular to a low-permeability and high-viscosity organic silicon encapsulation adhesive and a preparation method thereof. Background Art
[0002] The photoelectric effect caused by the hole-electron pairs of optoelectronic materials has a large number of applications in the energy field, such as LED / OLED, solar cells, etc. Optoelectronic devices, as carriers of photoelectric conversion, play a decisive role in energy conversion efficiency and utilization efficiency. Since optoelectronic materials are highly sensitive to water molecules and oxygen molecules in the air during the photoelectric conversion process, optoelectronic device packaging materials have strict requirements on the permeability of water vapor, oxygen and other molecules. For example, the water vapor permeability of OLED packaging must be very low to meet its long life requirements. Therefore, the water vapor permeability of optoelectronic device packaging glue must be reduced to meet the requirements. Since silicone encapsulation glue is resistant to high and low temperatures and excellent in weather resistance, and the silicone material chain segment is flexible, it is widely used in the field of optoelectronic devices, but its water vapor permeability is high and there are certain defects. Summary of the invention
[0003] In order to reduce the water vapor permeability of an organic silicon encapsulant, the present application provides a low-permeability high-viscosity organic silicon encapsulant and a preparation method thereof.
[0004] In a first aspect, the present application provides a low-permeability and high-viscosity silicone encapsulant, which adopts the following technical solution: A low-permeability high-viscosity organic silicon encapsulant, comprising a component A and a component B, wherein the weight ratio of the component A to the component B is 1:1, and the component A comprises the following raw materials in weight: 23-27 parts of methyl vinyl polysiloxane resin, 13-17 parts of vinyl-terminated silicone oil; based on the mass of platinum, 50 ppm of a platinum-based catalyst, and 90 ppm of tetramethyltetravinylcyclotetrasiloxane; The B component comprises the following raw materials in parts by weight: 22-28 parts of methyl vinyl polysiloxane resin, 15-25 parts of surface-modified nano-silicon dioxide, 4-8 parts of vinyl-terminated polydimethylsiloxane and 10-15 parts of end-side dihydrogenated silicone oil; The surface modified nano silicon dioxide is prepared by reacting nano silicon dioxide with a silane coupling agent containing double bonds, and then reacting the nano silicon dioxide with end-side double hydrogen-containing silicone oil through a silylation addition reaction.
[0005] By adopting the above technical scheme, the surface of nano-silica is coupled with a silane coupling agent with a double bond, and then reacts with the end-side double hydrogenated silicone oil under the catalysis of a platinum catalyst to undergo a silylation reaction, so that the hydrogenated silicone oil chain can be grafted on the surface of the nano-silica to obtain surface-modified nano-silica. After adding it to the silicone encapsulant, the silicon hydrogen groups on its surface can react with the double bonds in the encapsulant under the catalysis of the catalyst to undergo a silylation reaction for cross-linking, so that the surface-modified nano-silica forms a cross-linking center. On the one hand, the compatibility of inorganic particles in the encapsulant system can be enhanced, so that it can better fill the pores in the encapsulant, and can effectively reduce the water vapor permeability of the encapsulant; on the other hand, nano-silica as a cross-linking center can increase the cross-linking density and also effectively reduce the water vapor permeability of the encapsulant. Under the action of these two aspects, while reducing the water vapor permeability, the mechanical properties of the encapsulant are also greatly improved. The use of end-side double hydrogenated silicone oil can also increase the cross-linking degree of the encapsulant.
[0006] Preferably, the added amount of the surface modified nano-silica is 20 parts by weight.
[0007] By adopting the above technical solution, when the amount of surface modified nano-silica is gradually increased, its mechanical properties are gradually increased and the water vapor permeability is gradually reduced. However, when the amount of addition is continued from 20 parts by weight, the reduction in water vapor permeability and the improvement in mechanical properties are both small. Considering the production cost, 20 parts by weight is the optimal addition amount.
[0008] Preferably, the average particle size of the nano-silicon dioxide is ≤70 nm.
[0009] By adopting the above technical solution, the particle size of nano-silicon dioxide is a key factor affecting the performance of the encapsulation glue. As the particle size of nano-silicon dioxide gradually increases, its mechanical properties gradually decrease, and the water vapor permeability gradually increases. Therefore, the particle size of nano-silicon dioxide should not exceed 70nm. It is speculated that as the particle size of nano-silicon dioxide increases, the cross-linking density on its surface will decrease, thereby affecting the mechanical properties of the encapsulation glue.
[0010] As a preference: the preparation method of the surface modified nano-silica is as follows: S1. Add 4-8 parts by weight of nano-silicon dioxide to 100-200 parts by weight of ethanol, disperse by ultrasonication, heat to 40-50° C., add 20-26 parts by weight of a silane coupling agent containing a double bond, stir and react for 20-26 hours to obtain a solid, wash and dry to obtain silane coupling agent-modified nano-silicon dioxide; S2. Under nitrogen protection, add 1.5-3 parts by weight of silane coupling agent modified nano-silica to 90-110 parts by weight of toluene, disperse by ultrasonic, then add 5-20ppm of platinum catalyst, based on the weight of platinum, then add 70-80 parts by weight of end-side double hydrogenated silicone oil, stir to react for 8-12h, and vacuum desolventize to obtain surface-modified nano-silica.
[0011] By adopting the above technical scheme, after the surface of nano-silica is coupled with a silane coupling agent containing double bonds, its surface has double bonds, and then undergoes a silylation reaction with hydrogen-containing silicone oil to modify its surface. By selecting end-side double hydrogen-containing silicone oil, the surface of nano-silica can have more silicon-hydrogen bonds, which is more conducive to the silicon-hydrogen curing reaction of the encapsulation glue and the formation of nano-silica cross-linking centers.
[0012] Preferably, the double-bond-containing silane coupling agent is one or more of γ-methacryloxypropyltrimethoxysilane, vinyltriisopropoxysilane, tetramethyldivinylsiloxane, and vinyltributylacetonoximesilane.
[0013] By adopting the above technical solution, the silane coupling agent containing double bonds is selected within this range, and the expected technical effect can be obtained, which is not limited to the solutions listed in the embodiments.
[0014] Preferably, the component A further comprises 2-6 parts by weight of epoxy-terminated polydimethylsiloxane, and the component B further comprises 1-3 parts by weight of amino silicone oil.
[0015] By adopting the above technical solution, the degree of crosslinking can be improved through the ring-opening reaction of amino and epoxy groups, and the ring-opening curing of epoxy groups is equivalent to the addition of epoxy resin, which can further improve the mechanical strength of the encapsulation glue.
[0016] Preferably, the amino silicone oil is amino fluorosilicone oil.
[0017] By adopting the above technical solution and introducing fluorine atoms, the water vapor permeability can be further reduced.
[0018] Preferably, the methyl vinyl polysiloxane resin is vinyl MQ resin.
[0019] In a second aspect, the present application provides a method for preparing a low-permeability and high-viscosity silicone encapsulant, using the following technical solution: A method for preparing a low-permeability and high-viscosity organic silicon encapsulation adhesive comprises the following steps: S1. Preparation of component A: Control the temperature at 25-35°C, add methyl vinyl polysiloxane resin, vinyl-terminated silicone oil, tetramethyl tetravinyl cyclotetrasiloxane and platinum catalyst in sequence, stir and mix thoroughly under nitrogen protection, then evacuate, fill and seal for storage; S2, preparation of component B: control the temperature at 25-35°C, add methyl vinyl polysiloxane resin, surface modified nano-silica, end-vinyl polydimethylsiloxane, end-side dihydrogen silicone oil in sequence, and then add the remaining raw materials, stir and mix thoroughly under nitrogen protection, and then vacuumize and seal for storage; When in use, component A and component B are mixed in proportion, and cured at 25-35° C. for more than 24 hours to obtain the silicone encapsulation adhesive.
[0020] By adopting the above technical scheme, the product can be prepared by conventional stirring and mixing, vacuum degassing, and does not require high-temperature curing when used. It is suitable for large-scale production and is convenient and quick to use.
[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. After the surface of nano-silica is coupled with a silane coupling agent with double bonds, a silane-hydrogenated silicone oil with a platinum catalyst undergoes a silane-hydrogenated addition reaction, and a hydrogenated silicone oil chain can be grafted on the surface of nano-silica to obtain surface-modified nano-silica. After adding it to the silicone encapsulant, the silicon hydrogen groups on its surface can cross-link with the double bonds in the encapsulant through a silane-hydrogenated addition reaction under the catalysis of the catalyst, so that the surface-modified nano-silica forms a cross-linking center. On the one hand, the compatibility of inorganic particles in the encapsulant system can be enhanced, so that it can better fill the pores in the encapsulant, and can effectively reduce the water vapor permeability of the encapsulant; on the other hand, nano-silica as a cross-linking center can increase the cross-linking density and effectively reduce the water vapor permeability of the encapsulant. Under the action of these two aspects, while reducing the water vapor permeability, the mechanical properties of the encapsulant are also greatly improved. The use of end-side double hydrogenated silicone oil can also increase the cross-linking degree of the encapsulant.
[0022] 2. The tensile strength of the silicone encapsulant prepared in this application is between 6.36-8.82MPa, and after aging, it is above 5.84MPa; the elongation at break is between 241-423%, and after aging, it is between 175-392%; on the basis of excellent mechanical strength performance, its water vapor permeability is 6.09g / m 2 .24h.(2mm) and below, the minimum can reach 1.76g / m 2 .24h.(2mm), and after aging, they are all 7.68g / m 2 .24h.(2mm) or less, the lowest can reach 5.32g / m 2 .24h.(2mm); This indicates that the silicone encapsulation adhesive prepared in the application has excellent low permeability, and also has excellent mechanical properties and bonding strength. DETAILED DESCRIPTION
[0023] The present application is further described in detail below in conjunction with the specific contents.
[0024] raw material The raw materials used in the preparation examples and embodiments of the present application can all be purchased commercially, among which ethanol is anhydrous ethanol, the viscosity of the vinyl MQ resin is 10000mPas, and the vinyl content is 3wt%; terminal vinyl silicone oil; the viscosity of the terminal vinyl polydimethylsiloxane is 4000mPas; the viscosity of the terminal epoxy polydimethylsiloxane is 400cst, and the epoxy value is 0.015mol / 100g; the viscosity of the aminofluorosilicone oil is 1000mPas, the model is DF-HS-X, and the amino content is 0.2mmol / g; the viscosity of the amino-terminated polydimethylsiloxane is 5000mPas, and the nitrogen content is 0.6%.
[0025] Preparation Example Preparation Example 1 A surface modified nano silicon dioxide, the preparation method of which is as follows: S1. Add 6 g of nano-silica to 150 g of ethanol, disperse by ultrasonic for 30 min, heat to 45° C., add 22 g of a silane coupling agent containing a double bond, γ-methacryloxypropyltrimethoxysilane, stir and react for 24 h, centrifuge, filter to obtain a solid, wash with ethanol, and dry at 60° C. to obtain silane coupling agent-modified nano-silica; wherein the average particle size of the nano-silica is 30 nm; S2. Under nitrogen protection, 2 g of silane coupling agent modified nano-silica prepared by S1 was added to 100 g of toluene solution. After ultrasonic dispersion for 10 min, 10 ppm of Custer platinum catalyst was added, based on the mass of platinum, and stirred for 10 min. Then, 80 g of end-side double hydrogenated silicone oil (viscosity of 50 mPas and hydrogen content of 0.25 wt%) was added while stirring. Then, the reaction was stirred at 25 ° C for 10 h, and the solvent was removed in vacuo to obtain a solid with a sticky surface, i.e., surface-modified nano-silica.
[0026] Preparation Example 2 A surface-modified nano-silica, which is different from Preparation Example 1 in that the average particle size of the nano-silica is 50 nm, and the remaining steps are the same as Preparation Example 1.
[0027] Preparation Example 3 A surface-modified nano-silica, which is different from Preparation Example 1 in that the average particle size of the nano-silica is 70 nm, and the remaining steps are the same as Preparation Example 1. Example
[0028] Example 1 A low-permeability high-viscosity silicone encapsulant comprises a component A and a component B. The raw materials and amounts of the raw materials of the components are shown in Table 1. The preparation method thereof is as follows: S1. Preparation of component A: methyl vinyl polysiloxane resin, here vinyl MQ resin, take each raw material according to the amount of component A in Table 1, control the temperature at 30°C, add methyl vinyl polysiloxane resin, vinyl-terminated silicone oil, tetramethyl tetravinyl cyclotetrasiloxane and Custer platinum catalyst into a double planetary high-speed disperser in sequence, stir well for 1.5 hours under nitrogen protection, then evacuate, fill and seal for storage; S2, preparation of component B: methyl vinyl polysiloxane resin, here is vinyl MQ resin, take each raw material according to the amount of component B in Table 1, control the temperature at 30°C, then add vinyl MQ resin, surface modified nano-silica, terminal vinyl polydimethylsiloxane and terminal dihydrogen silicone oil into a double planetary high-speed disperser in sequence, stir well for 2 hours under nitrogen protection, and then fill and seal for storage after vacuumization; Wherein, the surface modified nano-silica is from Preparation Example 1; When in use, component A and component B are mixed in a mass ratio of 1:1, and then cured at 30° C. for 24 hours to obtain an organic silicone sealant.
[0029] Table 1 Raw materials and amounts of raw materials in Example 1 (kg) Component A Methyl vinyl polysiloxane resin 25 Vinyl-terminated silicone oil 15 Custer platinum catalyst 50ppm (based on the mass of platinum) Tetramethyltetravinylcyclotetrasiloxane 90ppm Component B Methyl vinyl polysiloxane resin 25 Surface modified nano-silica 20 Vinyl-terminated polydimethylsiloxane 12 End-side double hydrogen silicone oil 7 Example 2 A low-permeability and high-viscosity organic silicon encapsulant is different from Example 1 in that the surface-modified nano-silica comes from Preparation Example 2, and the remaining steps are the same as those of Example 1.
[0030] Example 3 A low-permeability and high-viscosity organic silicon encapsulant is different from Example 1 in that the surface-modified nano-silica comes from Preparation Example 3, and the remaining steps are the same as those of Example 1.
[0031] Example 4 A low-permeability and high-viscosity organic silicon encapsulation adhesive is different from Example 1 in that the amount of surface-modified nano-silicon dioxide added is 15 kg, and the remaining steps are the same as those of Example 1.
[0032] Example 5 A low-permeability and high-viscosity organic silicon encapsulation adhesive is different from Example 1 in that the amount of surface-modified nano-silicon dioxide added is 25 kg, and the remaining steps are the same as those of Example 1.
[0033] Example 6 A low-permeability and high-viscosity silicone encapsulant, which is different from Example 1 in that component A further includes 2 kg of epoxy-terminated polydimethylsiloxane, component B further includes 1 kg of aminofluorosilicone oil, and the remaining steps are the same as those of Example 1.
[0034] Example 7 A low-permeability and high-viscosity silicone encapsulant, which is different from Example 1 in that component A further includes 6 kg of epoxy-terminated polydimethylsiloxane, component B further includes 3 kg of aminofluorosilicone oil, and the remaining steps are the same as those of Example 1.
[0035] Example 8 A low-permeability and high-viscosity silicone encapsulant, which is different from Example 6 in that the aminofluorosilicone oil is replaced by amino-terminated polydimethylsiloxane of equal mass, and the remaining steps are the same as Example 6.
[0036] Comparative Example Comparative Example 1 A low-permeability and high-viscosity organic silicon encapsulant, which is different from Example 1 in that the surface-modified nano-silica in its B component is replaced by an equal mass of end-side double hydrogenated silicone oil, and the remaining steps are the same as Example 1.
[0037] Comparative Example 2 A low-permeability and high-viscosity organosilicon encapsulant is different from Example 1 in that the surface-modified nano-silicon dioxide in its component B is replaced by nano-silicon dioxide of equal mass, and the remaining steps are the same as those in Example 1.
[0038] Comparative Example 3 A low-permeability and high-viscosity organic silicon encapsulant is different from Example 1 in that surface-modified nano-silicon dioxide is not added to its component B, and the remaining steps are the same as those of Example 1.
[0039] Performance testing Detection method / test method The organic silicon encapsulating adhesives were prepared according to the preparation methods of Examples 1-8 and Comparative Examples 1-3, and then tested according to the following testing method. The test results are shown in Table 2.
[0040] Water vapor permeability: tested according to the test method in European standard EN1279-4; Tensile strength and elongation at break: Prepare samples according to Type 1 specimen in GB / T528-2009, and then test their tensile strength and elongation at break; Hot and cold cycle aging: Aging was carried out according to method 8.2 of GB / T36802-2018, and then the tensile strength, elongation at break and water vapor permeability of each sample were repeatedly tested.
[0041] Table 2 Test results of Examples 1-8 and Comparative Examples 1-3 Among them, the bonding strength of the silicone encapsulant prepared in Examples 1-8 of the present application is between 7.9-9.0 MPa.
[0042] It can be seen from the test data of Examples 1-8 and Comparative Examples 1-3, as well as Table 2, that the tensile strength of the silicone encapsulant prepared in the present application is between 6.36-8.82 MPa, and after aging, it is above 5.84 MPa; the elongation at break is between 241-423%, and after aging, it is between 175-392%; on the basis of excellent mechanical strength performance, its water vapor permeability is 6.09 g / m 2 .24h.(2mm) and below, the minimum can reach 1.76g / m 2 .24h.(2mm), and after aging, they are all 7.68g / m 2 .24h.(2mm) or less, the lowest can reach 5.32g / m 2 .24h.(2mm); This indicates that the silicone encapsulation adhesive prepared in the application has excellent low permeability, and also has excellent mechanical properties and bonding strength.
[0043] After the surface of nano-silica is coupled with a silane coupling agent with a double bond, a silane addition reaction occurs with the end-side double hydrogenated silicone oil under the catalysis of a platinum catalyst, and a hydrogenated silicone oil chain can be grafted on the surface of the nano-silica to obtain surface-modified nano-silica. After adding it to the organosilicon encapsulation glue, the silicon hydrogen groups on its surface can undergo a silane addition reaction with the double bonds in the encapsulation glue under the catalysis of the catalyst for cross-linking, so that the surface-modified nano-silica forms a cross-linking center. On the one hand, the compatibility of inorganic particles in the encapsulation glue system can be enhanced, so that it can better fill the pores in the encapsulation glue, and the water vapor permeability of the encapsulation glue can be effectively reduced; on the other hand, nano-silica, as a cross-linking center, can increase the cross-linking density and can also effectively reduce the water vapor permeability of the encapsulation glue. Under the action of these two aspects, while reducing the water vapor permeability, the mechanical properties of the encapsulation glue are also greatly improved. This can be verified by the test data of Example 1 and Comparative Examples 1-3. The surface of nano-silica is not modified, and it is easy to agglomerate in the encapsulation glue due to its interfacial tension and poor compatibility with the system, which is not conducive to the mechanical properties of the encapsulation glue.
[0044] The particle size of nano silicon dioxide is a key factor affecting the performance of the encapsulation glue. It can be seen from the test data of Examples 1-3 that as the particle size of nano silicon dioxide gradually increases, its mechanical properties gradually decrease and the water vapor permeability gradually increases. Therefore, the particle size of nano silicon dioxide should not exceed 70nm, and the smaller the better, but combined with the production cost, its particle size is preferably 30-50nm.
[0045] It can be seen from the test data of Example 1 and Example 4-5 that when the amount of surface-modified nano-silica added gradually increases, its mechanical properties gradually increase and the water vapor permeability gradually decreases. However, after its addition amount increases from 20kg to 25kg, the reduction in water vapor permeability and the improvement in mechanical properties are both small. In conjunction with Example 6-7, adding a certain amount of epoxy-terminated polydimethylsiloxane and aminofluorosilicone oil to the encapsulation glue can increase the degree of crosslinking through the ring-opening reaction of amino and epoxy groups, and the ring-opening curing of the epoxy group is equivalent to the addition of epoxy resin, which can further improve the mechanical strength of the encapsulation glue. In conjunction with Example 8, the water vapor permeability can be further reduced by the introduction of fluorine atoms through aminofluorosilicone oil at the same time.
[0046] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A low permeability and high viscosity silicone encapsulant, characterized in that: The invention comprises component A and component B, wherein the weight ratio of component A to component B is 1:1, and component A comprises the following raw materials in weight: 23-27 parts of methyl vinyl polysiloxane resin and 13-17 parts of vinyl-terminated silicone oil; based on the mass of platinum, 50 ppm of platinum-based catalyst and 90 ppm of tetramethyltetravinylcyclotetrasiloxane; The B component comprises the following raw materials in parts by weight: 22-28 parts of methyl vinyl polysiloxane resin, 15-25 parts of surface-modified nano-silicon dioxide, 4-8 parts of vinyl-terminated polydimethylsiloxane and 10-15 parts of end-side dihydrogenated silicone oil; The surface modified nano silicon dioxide is prepared by reacting nano silicon dioxide with a silane coupling agent containing double bonds, and then reacting the nano silicon dioxide with end-side double hydrogen-containing silicone oil through a silylation addition reaction.
2. The low permeability and high viscosity organic silicon encapsulant according to claim 1, characterized in that: The added amount of the surface modified nano-silica is 20 parts by weight.
3. The low permeability and high viscosity organic silicon encapsulant according to claim 1, characterized in that: The average particle size of the nano silicon dioxide is ≤70nm.
4. The low permeability and high viscosity organic silicon encapsulant according to claim 1, characterized in that: The preparation method of the surface modified nano silicon dioxide is as follows: S1. Add 4-8 parts by weight of nano-silicon dioxide to 100-200 parts by weight of ethanol, disperse by ultrasonication, heat to 40-50° C., add 20-26 parts by weight of a silane coupling agent containing a double bond, stir and react for 20-26 hours to obtain a solid, wash and dry to obtain silane coupling agent-modified nano-silicon dioxide; S2. Under nitrogen protection, add 1.5-3 parts by weight of silane coupling agent modified nano-silica to 90-110 parts by weight of toluene, disperse by ultrasonic, then add 5-20ppm of platinum catalyst, based on the weight of platinum, then add 70-80 parts by weight of end-side double hydrogenated silicone oil, stir to react for 8-12h, and vacuum desolventize to obtain surface-modified nano-silica.
5. The low permeability and high viscosity organic silicon encapsulant according to claim 4, characterized in that: The double-bond-containing silane coupling agent is one or more of γ-methacryloxypropyltrimethoxysilane, vinyltriisopropoxysilane, tetramethyldivinylsiloxane, and vinyltributylacetonoximesilane.
6. The low permeability and high viscosity organic silicon encapsulant according to claim 1, characterized in that: The component A further comprises 2-6 parts by weight of epoxy-terminated polydimethylsiloxane, and the component B further comprises 1-3 parts by weight of amino silicone oil.
7. The low permeability and high viscosity organic silicon encapsulant according to claim 6, characterized in that: The amino silicone oil is amino fluorosilicone oil.
8. The low permeability and high viscosity organic silicon encapsulant according to claim 1, characterized in that: The methylvinylpolysiloxane resin is a vinyl MQ resin.
9. A method for preparing the low-permeability and high-viscosity organic silicon encapsulant according to any one of claims 1 to 8, characterized in that: It includes the following steps: S1. Preparation of component A: Control the temperature at 25-35°C, add methyl vinyl polysiloxane resin, vinyl-terminated silicone oil, tetramethyl tetravinyl cyclotetrasiloxane and platinum catalyst in sequence, stir and mix thoroughly under nitrogen protection, then evacuate, fill and seal for storage; S2, preparation of component B: control the temperature at 25-35°C, add methyl vinyl polysiloxane resin, surface modified nano-silica, end-vinyl polydimethylsiloxane, end-side dihydrogen silicone oil in sequence, and then add the remaining raw materials, stir and mix thoroughly under nitrogen protection, and then vacuumize and seal for storage; When in use, component A and component B are mixed in proportion, and cured at 25-35° C. for more than 24 hours to obtain the silicone encapsulation adhesive.